Service Cloud for information retrieval from multiple origins - Oviedo, Néstor Fabián (2010)
One of the main intents of all digital libraries is to provide wide access to academic resources. Several tools and techniques are available to achieve this goal, some of them focus on harvest and storage of resources while others on retrieval and presentation. The heterogeneity of protocols, metadata formats and storage mechanisms generates a set of isolated datasources, which can be separately accessed by custom protocols and which usually contain only one part of the available information. This project suggests a solution for digital libraries based in a hybrid combination of software tools. The solution makes the procedure easier of information retrieval from heterogeneous datasources (OAI-PMH data provider, web services, z39.50, local repository, etc.) that can be queried from an arbitrary number of interfaces (OPAC, web services, z39.50, etc). Each of these entry points represent an unified view of the whole, which allows to easily interoperate across the interfaces and to collect, organize and return the results to the user that made the request. The development of this solution is based on the configuration of a set of special purpose tools. Additionally a set of adapters or drivers have been created, to allow the interoperability from and to each of the mentioned tools. The following tools have been considered so far in this project: an OAI harvester for harvesting bibliographic resources in any metadata format, Solr servers to index and retrieve information efficiently, a public OPAC, and finally a federated metasearch engine which works over the SRU/SRW and z39.50 standards. It is also possible to include other tools, which enables the opportunity add new services and data sources, without redesigning existing interfaces. Concepts developed along this work have been put into practice inside the Intellectual Creation Dissemination Service of La Plata National University. This initiative copes with a wide range of services for professors, researchers and students, such as: assisted search and provision of academic material in ISTEC and some non-ISTEC libraries, management and exposure of the institutional repository through OAI-PMH, public website to expose local and external resources (obtained via OAI-PMH) and harvesting of resources housed in academic units libraries of the University.